Ammonothermal Synthesis and Characterization of Cs2[Zn(NH2)4]. Issue 21 (7th October 2016) - Richter, Theresia M. M.; Alt, Nicolas S. A.; Schlücker, Eberhard; Niewa, Rainer
Abstract : Cs2 [Zn(NH2 )4 ] was synthesized under ammonothermal conditions (sc‐NH3, 523 K, 155 MPa) from CsNH2 and Zn. Growth of cm‐sized crystals succeeded upon application of a temperature gradient. The crystal structure is based on the motif of a hexagonal closed packing of [Zn(NH2 )4 ] 2– ions with occurrence of no significant hydrogen bridges according to distances and vibrational spectroscopy. Cs + ions are located within octahedral and tetrahedral holes of the packing. Abstract :